Transgressive edge play and Srpski Film/A Serbian Film. Issue 1 (1st April 2014) - Kimber, Shaun
Using Srpski Film/A Serbian Film (Spasojevic, 2010) as a case study this article examines transgressive edge play within contemporary horror film. The article starts by outlining two main assumptions: that transgression within horror cinema is customary rather than the exception; and that it is productive to study horror films holistically as a set of social and industrial practices, as an aesthetic object and as a social and cultural experience. The article then presents four overlapping contentions in relation to the complex ways in which A Serbian Film has engaged in transgressive edge play, in terms of its production contexts, aesthetics and narrative, and also the modes through which regulators, audiences and critics have responded to that boundary testing. An argument is developed, which contends that A Serbian Film, depending upon context and audience, has tested, infringed and also reinforced a gamut of thresholds in relation to what is contemporaneously tolerable within horror films.